Study on the strength composition mechanism and interface microscopic characteristics of cold recycling asphalt mixture - Dong, Zhao; Xu, Guangji; Xu, Shudong; Ma, Shijie; Ma, Tao; Luan, Yingcheng; Liu, Jiuwei (Frontiers in Materials, 2024)
A cold recycling asphalt mixture has significant economic and environmental benefits compared to other pavement material recycling technologies. The cold recycling mixture contains reclaimed asphalt pavement (RAP), new aggregate particles (NAPs), asphalt emulsion, cement, and fillers. The internal material composition is complex, and the interface form is changeable. Both have a significant impact on the mechanical properties. Therefore, this paper aims to study the influence of material composition and related content on the strength performance of a cold recycling mixture from the two aspects of macroscopic mechanical tests and microscopic characteristics analyses. In this paper, the strength evolution law of a cold recycling mixture under changed amounts of cement, emulsified asphalt, and RAP content is carried out. The test result shows that low cement content has little effect on the strength of a cold recycling mixture and is not the main factor affecting its strength composition. The asphalt mainly plays the role of a binder. Compared with the NAPs, the aged asphalt mortar and emulsified asphalt mortar have better interfacial bonding effects. The NAP surface needs more asphalt to form structural asphalt. From the microscopic characteristics of the interfacial transition zone, the cement hydration products and asphalt mortar are intertwined to form a network structure, and the pore structure is filled with asphalt. Compared with the aggregate–asphalt interface, the cement hydration product has poor adhesion with the aggregate. Some micro-cracks are visible in the interface transition zone, which is mainly used as an interface modifier and interface improver to enhance the interface bonding effect.